Wisatawan Paruh Waktu: Identifikasi Perilaku dan Motivasi Berwisata Mahasiswa Asing yang Menempuh Semester Pendek di Universitas Udayana - Suryasih, Ida Ayu; Indra Bhaskara, Gde (Jurnal Master Pariwisata (JUMPA), 2019)
This research is conducted to determine the behavior and motivation of foreign students traveling in Bali, especially those studying at Udayana University. Samples taken are foreign students who join short semesters in the GoBali International Program, IBSN and BIPAS. This research is important since foreign student market is being underestimated because it is considered to have low purchasing power, however tourism stakeholders seem to forget that they spend more time in the place where they study. By staying longer in Bali, there are two benefits to be gained. The first benefit is to support the local economy, because these foreign students stay for 20 weeks, it means they will rent a place to live, transport and spend their money. The second benefit is that foreign students will most likely explore places that hold the potential to become tourist attractions in the future. Indirectly, this foreign student will help stakeholders in tourism in identifying appropriate places to be made as tourist destinations. The methodology used to obtain data is preceded by a focus group to identify what factors need to be explored more in relation to their behavior and motivations in Bali. Then, after the factors are obtained, data collection through questionnaires is conducted to then use factor analysis, cluster analysis and compile the highest average values based on cluster groups, so that answers will be obtained on the degree of interests and behavioral tendencies of foreign students traveling in Bali. Keywords: foreign students, behavior, motivation, travel, short semester, udayana.